Using the extreme vertices mixture design approach to assess dulce de leche with whey - Gerson de Freitas Silva Valente; Ana Laís Andrade Gaspardi; Lara de Andrade Oliveira (Revista do Instituto de Latícinios Cândido Tostes, 2015)
This study aimed to use extreme vertices design approach to find the best formulation for dulce de leche with added whey. The assays were carried out with three components, namely sugar, milk, and whey, with three repetitions in the central point for a total of 11 assays. The extremes for milk and whey were 0 and 0.86 in mass fraction, while for sugar the extremes were 0.09 and 0.14. After 15 days, the product’s acceptance was analyzed for color, consistency, and flavor using a 9-point hedonic scale. The results show that the increase in whey content reduces product acceptance but that, for a score above 7.0 in hedonic scale (I like moderately), 0.35 of the mass fraction can be used in relation to milk, whey, and sugar components.